What do they need to know: achieving consensus on paediatric musculoskeletal content for medical students. Issue 1 (December 2015) - Jandial, Sharmila; Stewart, Jane; Foster, Helen
Abstract Background Children present commonly with musculoskeletal (MSK) problems, due to a spectrum of causes including potentially life threatening disease, to doctors in varied health care settings. However, doctors involved in the care of children report a lack of confidence in their paediatric musculoskeletal (pMSK) clinical skills and many have little exposure to pMSK teaching. There is no current guidance on the pMSK clinical skills and knowledge required for medical students. The objective of this study was to achieve consensus amongst experts on the learning outcomes for a pMSK curriculum for medical students. Methods This was a two-phase study. In Phase one, pMSK educational topics and categories were identified from UK medical students and experts (recruited from pMSK medicine, child health, education and primary care) utilising focus groups and interviews. These themes and concepts informed the structure of learning outcomes that were presented to a Delphi panel in Phase two, with the aim of achieving consensus on the final content of the curriculum. Results In Phase 1 participants identified pMSK skills, knowledge and attitudes relevant for medical students. This content was translated into learning outcomes. In Phase 2, the proposed outcomes were submitted to scrutiny by a two-iteration Delphi process with experts in the field. The agreed learning outcomes (n  = 45) were either generic to child health or specific to pMSK medicine, and related to history taking and examination, knowledge about normal development, key clinical presentation and conditions, approaches to investigation and referral pathways. Discussion This study has identified evidence and consensu based content for a pMSK curriculum for medical students, derived from key stakeholders and to be integrated into medical student pMSK teaching. Conclusion It is envisaged that implementation of this content will equip graduating doctors with relevant and important skills and knowledge to assess children with MSK presentations, and facilitate early diagnosis and referral to specialist care.